Structural and magnetic properties of hexagonal barium ferrite synthesized through the sol-gel combustion route - Zahari, M.H.B. (American Institute of Physics Inc., 2016)
Single-phased barium ferrite with the chemical formula of BaFe12O19 was synthesized through the sol-gel combustion method by using stoichiometric amounts of the precursor materials Structural characterizations were done through X-ray diffraction (XRD) analysis. The magnetic properties were determined through vibrating sample magnetometer (VSM) measurement. Pure single-phased BaFe12O19 was successfully obtained at 850Â°C without any accompanying secondary phases. This was reflected in the magnetic measurements where a prominent hysteresis was displayed by the synthesized powder. Values as high as 50.37 emu/g, 2984.9 G and 26.15 emu/g was observed for the magnetic saturation, coercivity and remanence respectively. Â© 2016 Author(s).